NUTRITIONAL EVALUATION OF SOME FORAGE PLANTS FROM KHUSHAB, PAKISTAN IN TERMS OF SEASONAL VARIATIONS (The Research of Medical Science Review, 2025)
Seasonal variations have been shown to influence the nutritional quality as well as chemical compositions of forage species. In this direction, this study critically investigated the changes in the proximate composition of various forage species during different sampling seasons (summer, autumn, winter &spring) in Khushab, Pakistan. During different samplings seasons 10 samples were collected in each season. Proximate analysis method was used for the study of crude protein, crude fibers, moisture contents, ether extract, ash and dry matter. The mean dry matter, moisture, crude protein, crude fibre, ether extract, ash and nitrogen free extract substance (NFES) contents in different sampling seasons were ranged from 89.87% to 94.15%, 5.84% to 10.13%, 16.23% to 19.04%, 14.49% to 16.64%, 0.77 % to 0.83%, 20.19% to 20.54%and 29.42% to 31.01%, respectively. Higher dry matter, crude fiber, ash and NFES percentage were found during summer sampling season, higher moisture and ether extract content were found during spring season and higher crude protein content was found during winter season. Keywords: Forage, proximate analysis, Pakistan.